Thermal Induced Clustering of Polysilicon Film on Silicon Nitride/Silicon Dioxide Bed on Silicon Substrate - Lamichhane, Shobha Kanta (Scientific World, 2010)
Polysilicon (PS) grains are clustered in an order in the presence of thermal doping of boron in low pressure chemical vapour deposition (LPCVD). PS layer is lying on Silicon Nitride/Silicon dioxide bed over (100) silicon substrate. The doped PS at different temperatures has been analyzed for the grain size and the shape of the clusters, employing non-contact mode Atomic Force Microscopy (AFM). The grain size of the PS remains intact without a significant change with increasing doping temperature. A substantial increase in the cluster size and its density of the grains has been observed. The cluster formation mechanism induced by thermal variation is discussed in the context of recorded AFM images. The clusters lead to PS rings comprising of grains of the size of 100 nm. Keywords: Doping; Polisilicon; Nanoscale; AFM; MEMS; LPCVD; Contactmode. DOI: 10.3126/sw.v8i8.3839 Scientific World Vol.8(8) 2010 pp.10-14